Thermal conductivity of nanocrystalline carbon films studied by pulsed photothermal reflectance - Shakerzadeh, Maziar (2013)
The effect of nanocrystals with preferred orientation on the thermal conductivity of carbon films is studied. During graphitization, the presence of biaxial compressive stress results in the formation of preferred orientation in the microstructure of graphitic nanocrystals if the corresponding activation energy is supplied. This formation of preferred orientation leads to the orientation of graphitic basal planes perpendicular to the substrate. Due to the high thermal conductivity of graphite in the basal planes, there is a significant increase in thermal conductivity of textured nanocrystalline films compared to amorphous film.